13-6x=-23

Simple and best practice solution for 13-6x=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-6x=-23 equation:



13-6x=-23
We move all terms to the left:
13-6x-(-23)=0
We add all the numbers together, and all the variables
-6x+36=0
We move all terms containing x to the left, all other terms to the right
-6x=-36
x=-36/-6
x=+6

See similar equations:

| 1/2y^2+3/4y=5 | | 10/m-10/m+5=1 | | d/65-3=d/130 | | x2(x-9)(2x+1)=0 | | 15-43y-6y^2=0 | | 5(3-3v)=15-3v | | 184=0,56x | | 6a+5=5+6a | | 3=(x-1)/(x+1) | | 10d/3=10 | | -13=5(1+4m-)-2m | | 15k^2+35k+25=90 | | 2x×x-16x+30=0 | | 17,5-7x=7 | | 7x-x=15 | | (9+2x)(3x-4)=0 | | (3x/7)-6=5 | | 5x^2-14x-16=0 | | x2+4x-1085=0 | | x+0.12x=6283 | | 8p+3=19 | | 22/7*r^2=490 | | (22/7)*r*r=500 | | 22/7*r*r=340 | | 47x=50 | | 48=7xX | | X+(x*5/100)=7695.24 | | 5y+3=24–2y | | X+(x*5/100)=3523.81 | | x8=6 | | ((3x+4)÷5)=4 | | 54=(1.5x-0.5) |

Equations solver categories